Surface Temperatures and Water Ice Sublimation Rate of Oxo Crater: A Comparison With Juling Crater. Issue 1 (3rd January 2019) - Formisano, M.; Federico, C.; Magni, G.; Raponi, A.; De Sanctis, M.C.; Frigeri, A.
Abstract: Dwarf planet Ceres is characterized by several sites hosting (or have hosted) ice‐rich patches as revealed by the Dawn's Visible and InfraRed spectrometer. The study of the illumination conditions including the effects of the local topography become critical in the estimation of the ice lifetime as well as the water vapor production rate. In this work we applied a 3‐D thermophysical model in order to study the illumination conditions on the shape model, derived on the basis of the images acquired by the Dawn's Framing Camera during the Survey mission phase, and to calculate the surface temperatures and water sublimation rates. We are interested in a crater in the northern hemisphere (42°), Oxo, which hosts water ice in its southern wall. A comparison with the surface temperatures and water sublimation rates of another Ceres' crater, Juling, is carried out. Water ice sublimation rate of its ice‐rich patch suggests that the Oxo crater probably is not the source of the emission detected by Herschel, a source that could be represented instead by the Juling crater. Plain Language Summary: There are several reasons to support the idea that the dwarf planet Ceres is a world with a huge presence of water. First of all, spectral evidence of water ice has been revealed by the Dawn's Visible and InfraRed spectrometer on the wall of some craters. Furthermore, both geomorphological evidence like surface flows and the presence of minerals, whose origin is correlated to the aqueous alteration, support this idea. Numerical simulations could contribute to understand how long the ice is stable on the surface, by studying the illumination conditions, and quantifies the eventual sublimation rate. In this work we concern about a particular crater, Oxo, in the northern hemisphere at latitude 42°, which hosts an ice‐rich patch in the southern wall. Key Points: We calculated the surface temperature and sublimation rates of Oxo crater by applying a 3‐D thermophysical model on real topography We compared the simulated temperatures with the VIR measurements Water emission rate suggests that Oxo is not the source of the emission detected by Herschel, while Juling probably is the best candidate